Design and Validation of Science Student Worksheet based on Argument Driven Inquiry to Improve Argumentation Skills for Junior High School Students - Lismawati Lismawati*; Neni Hasnunidah; Abdurrahman Abdurrahman (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
The survey results on teachers and students in six regencies/cities in Lampung Province showed that in science learning, teachers have not optimized the argumentative skills of students. Thus, this study aimed to develop and validate science worksheets oriented to the argumentative skills of students. This study used a 4D-study design with Argument-Driven Inquiry (ADI) learning model. A small-scale trial was conducted on 20 IX-graders at SMP 9 Krui Pesisir Barat. The large-scale trial was conducted on 50 IX-graders at SMP 9 Krui Pesisir Barat by purposive sampling with one experimental class and one control class. The control class used a worksheet from a particular publisher, and the experimental class used the developed worksheet. Based on the results, the ADI model worksheet can be declared valid in terms of content, construction, and language with an average of 92.3% with very high criteria. The practicality of the ADI worksheet model can be seen from the implementation of learning, student responses, and teacher responses had an average of 89.24% with very high criteria. The effectiveness of the ADI model worksheet can be seen from the ability to work on argumentation skills test questions, showing that the control class N-gain was 0.27 with low criteria and the experimental class was 0.57 with medium criteria. The effect size (SE) of 0.64 showed that the developed science worksheet was effective in developing argumentative skills of students with medium criteria